Kinematic models evaluation of shoulder complex during the badminton overhead forehand smash task in various speed. (2021) - Barnamehei, Hamidreza; Tabatabai Ghomsheh, Farhad; Safar Cherati, Afsaneh; Pouladian, Majid
Abstract: The badminton overhead forehand smash is a high-speed and high-risk action. The inverse kinematics analysis is a common way to calculate the joint kinematics during the overhead tasks. Different models are available to simulate various shoulder motions. The main aim of the current study was to understand which model is best to simulate the badminton overhead forehand smash. Twenty professional badminton players executed the badminton overhead forehand smash in front of ten motion captures. The marker data incorporated into four models in OpenSim software: (M1) a model with only three rotational degrees of freedoms between humerus and trunk Glenohumeral joint, (M2) a model with three rotational degrees of freedoms for Scapulothoracic joint, Acromioclavicular joint, and Glenohumeral joint, (M3) a model with coupled motions for scapula, clavicle, and humerus, (M4) a model with an ellipsoid mobilizer for the Sternoclavicular joint. The marker error and kinematics variables were used as indicators. The primary assumption was that the privileged model would eventuate in the lowest marker error. Based on results the significant differences were observed between generics and scaled models. Results showed model M1 as the worst model that only modeled shoulder complex by the glenohumeral joint. In addition, the best model was M4 that modeled the joint between the scapula and the trunk by a contact ellipsoid. In addition, no significant differences were observed among various speeds (slow, normal, and fast) that indicated the selection of model didn't depend on the speed of movements.